ROLE OF IRON, ZINC AND ORGANIC NUTRIENT ON YIELD OF GREEN BEANS - & Al-jumaili, Al-dulaimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out in the agricultural research station of the College of Agriculture-University of Baghdad, during the seasons spring and autumn 2015, use in agriculture beans hybrid primal seeds, one of the short variety. The aim of the experiment to study the effect of iron, zinc spray and add the organic nutrient on yield of green beans (Phaseolus vulgaris L.), The experiment was designed factorial experiment (3*4) with three replications according to the experimental design (RCBD), the first factor four spray treatments (0 and Zn 0.5 ml L-1 water and Fe 2 g L-1 water and Fe+Zn), the second factor adding three levels of humic acid ( 0, 2, and 3)kg ha-1 after melted in a calculated amount of water and add in a groove around the plants for each experimental unit. Results showed the superiority of the treatment of interaction M4H2 (3 kg ha-1Humic acid + Fe+Zn) in pod length 17.67 and 15.23cm pod-1, a number pods 18.62 and 18.65 pod plant-1, weight pod 9.65 and 7.18 g plant-1, number of seeds in pod 6.36 and 6.65 seed pod-1, seed weight 0.174 and 0.165g seed-1, early yield 1.613 and 1.482 ton ha-1 and total yield 14.13 and 10.72 ton ha-1, for two seasons, spring and autumn for every traits respectively .